Cellular imaging and mitochondria targeted photo-cytotoxicity in visible light by singlet oxygen using a BODIPY-appended oxovanadium(iv) DNA crosslinking agent12. Issue 7 (27th May 2016) - Kumar, Arun; Dixit, Akanksha; Banerjee, Samya; Bhattacharyya, Arnab; Garai, Aditya; Karande, Anjali A.; Chakravarty, Akhil R.
Abstract : Targeted PDT by 1 O2 at mtDNA crosslinking site of a BODIPY-appended VO 2+ complex in visible light. Abstract : Oxovanadium(iv ) complexes [VO(L 1 )Cl2 ] (1 ) and [VO(L 2 )Cl2 ] (2 ), where L 1 is N, N, N-donor benzyldipicolylamine and L 2 is the BODIPY-appended N, N, N-donor base, viz., (8-{[bis(2-pyridylmethyl)amino]methylphenyl}-4, 4-difluoro-1, 3, 5, 7-tetramethyl-4-bora-3a, 4a-diaza-s-indacene), were synthesized, characterized and their photo-induced DNA crosslinking activity and photocytotoxicity were studied. Single crystal X-ray diffraction analysis of1 reveals two chloride ligands in the cis disposition to the VO 2+ moiety. The complexes are 1 : 1 electrolytes in aqueous media, and the loss of the second chloride takes place on irradiation with visible light. The DNA melting and alkaline agarose gel electrophoresis studies on complex2, treated with ct-DNA in light, suggest the formation of DNA crosslinks. Complex2 selectively localizes in the mitochondria of the HeLa and MCF-7 cancer cells and shows remarkable photocytotoxicity via an apoptotic pathway (IC50 < 3 μM) in visible light (400–700 nm) with low dark toxicity. The complex is remarkable in showing dual activity: (i) light-activated VO 2+ –DNA crosslink formation and (ii) singlet oxygen ( 1 O2 ) induced mitochondria-targeted PDT involving the BODIPY moiety.